2020
DOI: 10.1016/s2214-109x(20)30034-6
|View full text |Cite|
|
Sign up to set email alerts
|

Performance of late pregnancy biometry for gestational age dating in low-income and middle-income countries: a prospective, multicountry, population-based cohort study from the WHO Alliance for Maternal and Newborn Health Improvement (AMANHI) Study Group

Abstract: Background We aimed to evaluate and improve the accuracy of the ultrasound scan in estimating gestational age in late pregnancy (ie, after 24 weeks' gestation) in low-income and middle-income countries (LMICs), where access to ultrasound in the first half of pregnancy is rare and where intrauterine growth restriction is prevalent. Methods This prospective, population-based, cohort study was done in three LMICs (Bangladesh, Pakistan, and Tanzania) participating in the WHO Alliance for Maternal and Newborn Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Compared with the conventional, more complex circumferential measurements of abdominal circumference (AC) and head circumference (HC), measurement of the FL requires only an image of a straight bone, making it a much easier measurement to obtain ( 6 , 32 ). The reported difference in the gestational age assigned by FL alone is only ±2.4 days at <24 + 0 weeks, ±1.7 days at 24–29 + 6 days and ±1.8 days at >30 + 0 weeks ( 33 ). We believe that utilizing this approach has the potential to maximize the sustainability and implementation of this US training program without compromising clinical care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the conventional, more complex circumferential measurements of abdominal circumference (AC) and head circumference (HC), measurement of the FL requires only an image of a straight bone, making it a much easier measurement to obtain ( 6 , 32 ). The reported difference in the gestational age assigned by FL alone is only ±2.4 days at <24 + 0 weeks, ±1.7 days at 24–29 + 6 days and ±1.8 days at >30 + 0 weeks ( 33 ). We believe that utilizing this approach has the potential to maximize the sustainability and implementation of this US training program without compromising clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of consensus on the assessment of competency in obstetric ultrasound and a number of previous programs have omitted practical assessment completely ( 27 , 31 , 35 , 38 40 ). The OSCE approach to “hands-on” assessment is well-established ( 24 , 26 , 28 , 30 , 41 ), as is the concept of comparing trainee measurements with those obtained by the faculty ( 20 , 22 , 23 , 33 , 42 ). By combining these, we sought to ensure that all aspects of our curriculum were assessed, with trainees demonstrating their ability to explain and document their findings as well as obtain accurate results.…”
Section: Discussionmentioning
confidence: 99%
“…This holistic approach may account for the increased accuracy later in the pregnancy, when the correlation between GA and physical size of the fetus is less pronounced. This may be especially helpful in providing more accurate estimated GA in LMIC settings where access to ultrasound in early pregnancy is rare 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggested that using US in second/third trimester with a novel parsimonious formula might narrow accuracy to ± 10.5 days (between 24 0/7 weeks and 29 6/7 weeks of gestation) and of ± 15.1 days (between 24 0/7 weeks and 29 6/7 weeks of gestation) [ 14 ]. These results suggest that concentrating efforts and resources in further validating and implementing the use of late pregnancy biometry for gestational age assessment may be valuable in settings where the preferred reference standards are unavailable.…”
Section: Discussionmentioning
confidence: 99%